Nghiên cứu chế tạo vật liệu nanocompozit trên cơ sở hỗn hợp một pha, hai pha của các nhựa polyeste không no và nanosilica - Sơn và cộng sự, Hoàng Anh (Vietnam Journal of Chemistry, 2014)
Phytochemical investigation on Gymnotheca chinensis Decne growing in Vietnam led to the isolation of three pentacyclic tritecpenoids. On the basis of spectroscopic data, the structures of these compounds were established as 3b-hydroxy-olean-12-en (b-amyrin, I), 3b-hydroxy-urs-12-en-28-oic acid (ursolic acid, II) and 3b-acetoxy-urs-12-en-28-oic acid, (3b-acetoxy ursolic acid, III).